A STUDY ON STUDENTS’ ABILITY IN WRITING HORTATORY EXPOSITION TEXTS - Dwi Setyawan (INOVISH JOURNAL, 2016)
Abstract: The purpose of this research was to find out the students’ abilty in writing hortatory exposition text at class XI SMA YLPI Perhentian Marpoyan Pekanbaru. This research was conducted on April to May 2010. The sample of the research was the students of class XI SMA YLPI Perhentian Marpoyan Pekanbaru. There were 76 students as the sample of the research. They were class XI IPS1, XI IPS2 and XI IPA. The instrument of the research was the writing test that required the students to write a hortatory exposition text. The test was analyzed by two different raters. It can be concluded that level of ability of the second year students of SMA YLPI Perhentian Marpoyan pekanbaru in writing hortatory exposition text was in mediocre level 55.26% (21 students). Key word: The Students’ Ability, Writing, Hortatory Exposition Text.